Comparison of gross visual and microscopic assessment of four anatomic sites to monitor Besnoitia tarandi in barren-ground caribou (Rangifer tarandus groenlandicus) - Brodeur, Vincent; Beauchamp, Guy; Côté, Steeve D.; Kutz, Susan; Taillon, Joëlle; Simard, Manon; Elkin, Brett; Ducrocq, Julie; Croft, Bruno; Campbell, Mitch; Cooley, Dorothy; Cuyler, Christine; et al. (Journal of Wildlife Diseases, 2020)
The objective of this study was to establish a standardized protocol to monitor Besnoitia tarandi prevalence and intensity in barren-ground caribou (Rangifer tarandus) herds by: 1) calculating the relative sensitivity and specificity of the gross visual assessment of four anatomical sites compared with microscopic evaluation, and 2) determining which of four anatomical sampling sites was the most sensitive for detecting B. tarandi cysts by microscopy. Sampled tissues consisted of the conjunctiva of the left eye and skin sections from the rostrum, metatarsus, and thigh from 312 harvested caribou. Diagnosis of infection with B. tarandi was based on observation of at least one cyst by microscopic examination. For each tissue, the maximal density of cysts (number of B. tarandi cysts/mm(2) in the section examined) was calculated for a measured area consisting of the dermis extending from the epidermis of the skin to the base of the hair follicles and adnexal structures. For the conjunctiva, the entire submucosa was evaluated. Gross visual evaluation markedly underestimated B. tarandi prevalence in caribou with a relative sensitivity ranging from 0.29 in the conjunctiva to 0.13 in the skin section from the thigh, whereas relative specificities ranged from 0.98 to 1.00. The metatarsus and rostrum skin sections had the highest probabilities of cyst detection of all four anatomical sampling sites. The metatarsus harbored significantly higher densities of B. tarandi cysts than the rostrum, thigh, or conjunctiva. In conclusion, microscopic evaluation of a skin section from the anterior aspect of the mid-third portion of the metatarsal region could be used as a standardized comparative indicator of density of B. tarandi infection in Rangifer.